THE EFFECT OF MUNTINGIA CALABURA ETHANOLIC LEAVES EXTRACT FOR ASPIRIN-INDUCED GASTRIC MUCOSAL DAMAGE - Almaarif Faiq Rizky; Eva Annisaa'; Nani Maharani; Astika Widy Utomo (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background: Muntingia calabura leaves have been claimed to relieve pain, fever, inflammation, and many others. Many studies has already prove the potential of these leaves as anti-inflammation, anti-nociceptive, and anti-proliferative. It might have capability to protect gaster from ulcer. Objective: This study aimed to know the effect of Muntingia calabura ethanolic leaves extract (MCELE) for aspirin-induced gastric mucosal damage on wistar rats. Methods: Twenty-five wistar rats is divided into 5 groups. K2 group (aspirin 300 mg/kg. K1, P1, P2, and P3 group received misoprostol 100 mcg/kg, MCELE 100 mg/kg, MCELE 250 mg/kg, and MCELE 500 mg/kg respectively 1 hour before the administration of aspirin 300 mg/kg. All treatments were administered orally once daily for 7 consecutives days. On day 8, all rats were sacrificed, and gastric tissues were collected for histopathological examination. The tissues were stained with hematoxylin and eosin (H&E) and evaluated under light microscopy to assess mucosal damage, including desqumasion, epithelial erosion, and ulceration. Statistical analysis was performed using the Kruskal-Wallis test, followed by the Mann-Whitney test for pairwise comparisons. Differences were considered statictically siginificant at p<0.05. Results: Histopathology test result showed a significant difference between K1 group and K2 group (p=0.003). Each treatment group also showed a significant difference when compared to K2 group (p<0.05). P3 group and K1 group showed a similar effect on rat’s gastric mucosa (p=1.000). Conclusion: Administration of MCELE may lower gastric mucosal damage on wistar rats induced by aspirin, with 500 mg/kg dose is almost as effective as standard drugs (Misoprostol).